Personal correspondence - Gassama, Abdou; Abrahams, Peter; Glave, Hal; Gustafson, Winifred; Hibbert, Alvy; Hippolyte, J. M.; Ho Ken, Elsa; Hogbin, Phyllis; Hughes, Langston; Hylton, T. B. (My University, 1984)
Personal correspondence between Peter Abrahams and various individuals (E-F)
58 pgs. Typescript and handwritten, sepia-toned, fragile condition
Keywords: Letters; Abrahams, Peter, 1919-2017 - Correspondences